Daily versus post-dialysis administration of calcimimetics for the treatment of secondary hyperparathyroidism in haemodialysis patients: an interventional, multi-centre study [article retracted] - Demerdash, Tarek M; Abdelsalam, Mostafa; Assem, Mohammed; Shaheen, Mahmoud M; Marie, Mohamed A (African Journal of Nephrology, 2020)
This article has been retracted. The retraction notice was published on 06 May 2020: Retraction notice: Daily versus post-dialysis administration of calcimimetics for the treatment of secondary hyperparathyroidism in haemodialysis patients: an interventional, multi-centre study. Afr J Nephrol. 2020; 2391):85.